A STUDY ON THE EFFECT OF FOOD HABITS AND LIFE STYLE ON THE HEALTH OF ADOLESCENTS : IN CONTEXT OF DHANDBAD DISTRICT - Chandra Prabha; Verma, Chanchala (International Journal of Research -GRANTHAALAYAH, 2024)
The present study investigated the prevalence of life style and eating habits related concerns among adolescents. The data was collected from 300 adolescents studying in the two main institutions situated at Dhanbad district. The study documents the multiple concerns related to inappropriate dietary practices (fast food consumption, cold drinks, low fruits and vegetable intake), irregular sleeping habits, less religiosity, mild activity pattern, unhealthy daily routine and pursuance of different forms of risk behaviours. Nutrition behaviour and lifestyle pattern were studied using the standardized schedule. The collected and analysed data showed that there is a positive correlation between the health status, life style and dietary habits.